Synthesis and Antimicrobial Activity of Alkyl-2-{[3-(3'-Chloro-4'-Nitrophenyl)-2-Oxo-3, 4-Dihydro-2h-1, 3, 2l5-Benzoxazaphosphinin-2-Yl]Amino} Alkanoates - K.SURESH KUMAR; N.BAKTHAVATCHALA REDDY; K. UMA MAHESWARA RAO; SK.ANNAR; C.SURESH REDDY (International Journal of Pharma and Bio Sciences, 2010)
Synthesis of alkyl-2-{[3-(3'-chloro-4'-nitrophenyl)-2-oxo-3,4-dihydro-2H-1,3,2λ5-benzoxazapho sphinin- 2-yl]amino} alkanoates (4a-j) were accomplished via a two-step process, involving the condensation of 2-[(3'-chloro-4'-nitrophenyl amino)methyl]phenol (1) with phosphorusoxychloride in the presence of triethylamine (TEA) in dry tetrahydrofuran (THF) to produce the corresponding monochloride intermediate (2), and subsequent reaction with the amino acid alkyl ester in dry THF in the presence of TEA at various temperatures. These compounds were characterized by IR, 1H, 13C, 31P NMR and mass spectral data and all them exhibited significant antibacterial and fungal activity